If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + -7) = 5n + 3 + -2n Reorder the terms: 3(-7 + n) = 5n + 3 + -2n (-7 * 3 + n * 3) = 5n + 3 + -2n (-21 + 3n) = 5n + 3 + -2n Reorder the terms: -21 + 3n = 3 + 5n + -2n Combine like terms: 5n + -2n = 3n -21 + 3n = 3 + 3n Add '-3n' to each side of the equation. -21 + 3n + -3n = 3 + 3n + -3n Combine like terms: 3n + -3n = 0 -21 + 0 = 3 + 3n + -3n -21 = 3 + 3n + -3n Combine like terms: 3n + -3n = 0 -21 = 3 + 0 -21 = 3 Solving -21 = 3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 5x-11=8x-20 | | e-f=11 | | 86Y-29=Y-39 | | 1/3(21x+18)=23-2(x-5) | | -(2x-4)=3(2x-8) | | p-(17)=23 | | 2x^3-13x^2+16=0 | | -2x-6=-6x-38 | | (y+2)=8+4y | | n/3-3n/4=5/12 | | 3+x=6x+23 | | 38.35(n)=25+0.15n | | 4x-9=x-30 | | 4x+54=3x-7 | | 5x*1.41=8 | | 5x+2=1/2(10x+4) | | 2x(x+3)=2x+15 | | 3r=5.1 | | -16*2+36=0 | | 2x+9=-3x+59 | | -2y-5x=14 | | x+(x-2)+1.5x=12 | | h^2-4(h)(-1)=0 | | x*1.73=9 | | 18=-20x | | 7x/5=x-4 | | 1-4(h)(-h)=0 | | x^4=27x | | 18z^2-48z-130=0 | | 9y-6=3 | | 1+4h^2=0 | | -3*-y= |